Efektivitas Model Pembelajaran Project Based Learning dalam Meningkatkan Kreativitas dan Kemampuan Numerasi Siswa - Sahila, Linda; Supratman, Moh; Rahmawati, Helmi (Tirai Edukasi : Jurnal Pendidikan, 2025)
This study aims to examine the effectiveness of the Project Based Learning (PjBL) model in improving seventh-grade students’ creativity and numeracy skills at MTs NW Pringgarata. The main issue addressed is the low level of creativity and numeracy skills caused by conventional teaching methods. A quantitative quasi-experimental design was employed, involving two groups: an experimental class implementing PjBL and a control class using traditional methods. Research instruments included creativity and numeracy tests, supported by assessment rubrics, with data collected through pretests and posttests. Data analysis applied t-tests and N-Gain calculations. The results show that PjBL significantly improves students’ creativity and numeracy skills. The experimental class achieved higher posttest scores than the control class, with an N-Gain of 0.60 (moderate category) compared to 0.49 (moderate category). These findings indicate that PjBL is an effective and innovative alternative teaching method to enhance students’ creativity and numeracy skills.